Altered Synaptic Properties During Integration of Adult-Born Hippocampal Neurons Following a Seizure Insult - Jackson, Johanna; Chugh, Deepti; Nilsson, Per; Wood, James; Carlström, Karl; Lindvall, Olle; Ekdahl, Christine T. (PLOS ONE, 2012)
Pathological conditions affect several stages of neurogenesis in the adult brain, including proliferation, survival, cell fate, migration, and functional integration. Here we explored how a pathological environment modulates the heterogeneous afferent synaptic input that shapes the functional properties of newly formed neurons. We analyzed the expression of adhesion molecules and other synaptic proteins on adult-born hippocampal neurons formed after electrically-induced partial status epilepticus (pSE). New cells were labeled with a GFP-retroviral vector one week after pSE. One and three weeks thereafter, synaptic proteins were present on dendritic spines and shafts, but without differences between pSE and control group. In contrast, at six weeks, we found fewer dendritic spines and decreased expression of the scaffolding protein PSD-95 on spines, without changes in expression of the adhesion molecules N-cadherin or neuroligin-1, primarily located at excitatory synapses. Moreover, we detected an increased expression of the inhibitory scaffolding protein gephyrin in newborn but not mature neurons after SE. However, this increase was not accompanied by a difference in GABA expression, and there was even a region-specific decrease in the adhesion molecule neuroligin-2 expression, both in newborn and mature neurons. Neuroligin-2 clusters co-localized with presynaptic cholecystokinin terminals, which were also reduced. The expression of neuroligin-4 and glycine receptor was unchanged. Increased postsynaptic clustering of gephyrin, without an accompanying increase in GABAergic input or neuroligin-2 and -4 expression, the latter important for clustering of GABAA and glycine receptors, respectively, could imply an increased but altered inhibitory connectivity specific for newborn neurons. The changes were transient and expression of both gephyrin and NL-2 was normalized 3 months post-SE. Our findings indicate that seizure-induced brain pathology alters the sub-cellular expression of synaptic adhesion molecules and scaffolding proteins related to particularly inhibitory but also excitatory synapses, which may yield functional consequences for the integration of adult-born neurons.